Effects of deep knee flexion on skin pressure profile with lower limb device: A computational study. Issue 17 (September 2020) - Lin, Yinglei; Li, Yi; Yao, Lei; Zhao, Guoru; Wang, Lei
Knee flexion behavior alters the contact pressure distribution exerted by compression devices during exercise. This study aimed to develop a three-dimensional dynamic finite element model of the lower limb with detailed bony structures, wearing a compression device with higher pressure over the calf, and then to quantify and compare the garment–body interface contact pressure and the cross-section pressure gradient deviation in standing and deep knee flexion postures (30°, 60°, 90°, and 120° of knee flexion). Contact pressure experiment on seven muscle points was applied to validate the model. The cross-section pressure gradient deviation was calculated on landmarks based on deviation along the four axial pathways from the average cross-section pressure gradients. In general, the results demonstrated that the whole pressure profile gradually decreased from the ankle to the thigh with higher compression on the calf in a standing position. Cross-section pressure gradient deviation resulted in a dramatic increase of ∼100% and ∼110% on positions B1 and D on the anterior of calf at 60° flexion, respectively, which resembled an M shape. This phenomenon was caused by the combination of the stretch of clothing during knee flexion, high compression over the calf, and the shape of the lower limb. This finite element model and its findings together could help us to understand the compression effects of sports lower limb devices and garments to enhance walking and running performance, and help to improve the design concepts.